Continental powers and naval development : strategy soherence, threat diffusion, and success at sea - Chao, Brian C. (Cass series--naval policy and history, 2026)
This book examines how continental great powers have attempted to develop and wield strong navies since 1801.Continental Powers and Naval Development argues that a continental great power's ability to build and effectively use a strong navy is greatly affected by two factors: a naval force design capable of executing national strategy (strategy coherence) and the deployment of that navy to places or for purposes that minimize the dominant naval power's threat perception (threat diffusion). Each factor is deceptively difficult for a continental great power to achieve but, through an analysis of four historical case studies, this book shows how both factors are vital not just for successful naval development, but for keeping the peace among great powers. Finally, it highlights how states commonly thought of as "unnatural" naval powers can nonetheless achieve their political objectives at sea.This book will be of much interest to students of naval history, maritime strategy, and International Relations.